Horn, Eva, Bergthaller, Hannes, (2020). The Anthropocene: Key Issues for the Humanities - Fuchs, Susanne (Journal of Ecohumanism, 2023)
Horn, Eva, Bergthaller, Hannes, (2020). The Anthropocene: Key Issues for the Humanities, Routledge, 2020, 192 pages, 14 B/W illustrations. US44,95 ISBN: 9781138342477